2020
DOI: 10.1063/5.0024264
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulations of airflow and particle deposition in pulsating bi-directional nasal drug delivery

Abstract: Chronic rhinosinusitis is a common disease worldwide, and the frequently prescribed nasal sprays do not sufficiently deliver the topical medications to the target sites so that the final treatment in severe cases is surgery. Therefore, there is a huge demand to improve drug delivery devices that could target the maxillary sinuses more effectively. In the present study, different particle diameters and device pulsation flow rates, mainly used in pulsating aerosol delivery devices such as the PARI SINUS®, are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The validity of the present numerical solver was assessed in two steps. In our previous publications ( Farnoud et al, 2017 ; Farnoud et al, 2020a ; Farnoud et al, 2020b ), the DE in 90° bends was compared to the experimental data of Pui et al (1987) and other research in the literature ( Breuer et al, 2006 ; Nicolaou and Zaki, 2016 ; Inthavong, 2019 ) to ensure that the solver is able to capture the DE of particles correctly. This benchmark is a popular approach to validate the capability of a numerical solver to predict particle deposition in curvature geometries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of the present numerical solver was assessed in two steps. In our previous publications ( Farnoud et al, 2017 ; Farnoud et al, 2020a ; Farnoud et al, 2020b ), the DE in 90° bends was compared to the experimental data of Pui et al (1987) and other research in the literature ( Breuer et al, 2006 ; Nicolaou and Zaki, 2016 ; Inthavong, 2019 ) to ensure that the solver is able to capture the DE of particles correctly. This benchmark is a popular approach to validate the capability of a numerical solver to predict particle deposition in curvature geometries.…”
Section: Resultsmentioning
confidence: 99%
“…A three-dimensional geometry of the nasal cavity and paranasal sinuses was reconstructed from CT images of a male, 82-year-old patient, as previously studied by Farnoud et al (2017) , Farnoud et al (2020a) , and Farnoud et al (2020b) . The CT images were segmented using the open source software package 3DSlicer.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Basu et al [ 9 ] suggested new methods to enhance the deposition efficiency of micro-aerosols and used 3D printed replicas to validate the numerical results. Several researchers have studied the micro-aerosols delivery into different regions of the nasal cavity such as maxillary sinuses, olfactory regions and turbinates [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In recent years, different methods such as imposing conditions of pulsatile airflow [ 12 , 13 , 19 ], acoustic waves superposition [ 10 , 11 , 20 ], and swirling flow [ 14 ] at the nostrils have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that drug delivery with pulsating inlet airflow resulted in a more uniform deposition pattern compared to non-pulsating flow in the nasal airways. In another study, Farnoud et al [ 13 ] studied the effect of flow rate and micro-aerosol size on deposition efficiencies in the nasal cavity, specifically the maxillary sinuses. They observed enhancement in deposition efficiency by applying a bi-directional delivery method.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) provides a technique to predict fluid flows (both air and liquid phases) through the rigid sinonasal cavities that is quantifiable and reproducible under different conditions (Lee et al, 2016;Patki and Frank-Ito, 2016;Tong et al, 2016;Calmet et al, 2019;Frank-Ito et al, 2019;Inthavong, 2020). Recent work has demonstrated the applicability of CFD for investigating different nasal therapies, including thermal water delivery (Covello et al, 2018); bidirectional pulsating nasal aerosol dispersion (Farnoud et al, 2020a(Farnoud et al, , 2020b; nebulisers and sprays (Farzal et al, 2019); and also the effects of nasal dilation on olfactory deposition during unilateral and bi-directional delivery (Xi et al, 2018). Furthermore, models of nasal irrigation have been generated using CFD (Zhao et al, 2016;Craig et al, 2017;de Gabory et al, 2020;Inthavong et al, 2020;Salati et al, 2020) which has increased understanding of nasal irrigation and provided insight to how its effectiveness can be improved.…”
Section: Introductionmentioning
confidence: 99%